Effect of body position on qualitative and quantitative ultrasound assessment of gastric fluid contents1. (8th April 2019) - Bouvet, L.; Barnoud, S.; Desgranges, F.‐P.; Chassard, D.
Summary: We assessed the impact of raising the upper section of the bed, and patient positioning, on ultrasound assessment of gastric fluid contents. We performed ultrasound examinations in 25 subjects lying on their back, left and right sides at bed angles of 0°, 30°, 45° and 90°; this was carried out while the subjects were fasted, and repeated 10 min after drinking ≥ 50 ml water. After drinking, gastric contents were detected more frequently in the 45° semirecumbent position compared with the supine and 30° positions. The diagnostic performance of the Perlas qualitative grading scale to detect gastric fluid volume > 1.5 ml.kg −1 was improved at 45°, compared with 0° and 30° angles. The use of a composite ultrasound grading scale at a 45° angle was associated with the best performance, with a sensitivity and specificity of 82%. Antral cross‐sectional area was significantly increased when measured in the right lateral position, but there was no effect of raising the bed. In conclusion, raising the upper section of the bed significantly affected qualitative assessment of gastric fluid contents. Further studies are required to determine the most appropriate composite ultrasound grading scale and bed angle for fast and reliable qualitative ultrasound detection of fluid volumes > 1.5 ml.kg −1 .